Factors Associated With Toddlers’ Visit At Village Integrated Healthcare Center - Siti Mariyam; Tuti Farida; Sri Handayani (JKM (Jurnal Kebidanan Malahayati), 2023)
Latar Belakang: Balita termasuk salah satu kelompok yang berisiko terhadap masalah kesehatan.Data Dinas Kesehatan Provinsi Sumatera Selatan Cakupan D/S pada tahun 2018 belum mencapai target 85%, baru mencapai 73,2% (669,814 balita) dari 914,527 balita. Angka ini mengalami penurunan dibanding tahun 2017 (75,99%). Cakupan D/S belum mencapai target antara lain disebabkan efektifitas kegiatan posyandu dan kegiatan luar puskesmas belum optimal. Data profil posyandu di desa Marga Bakti sasaran balita umur 0-59 tahun 2.671 balita, pada tahun 2020 terdapat jumlah Balita yang berkunjung  sebanyak 548. Dampak anak balita yang tidak dibawa ke posyandu diantaranya tidak terpantaunya status gizi anak, balita akan menderita penyakit seperti hepatitis, campak, tuberculosis apabila tidak diimunisasi, dan paling utama yaitu akan meningkatnya kasus kematian anak balita.Tujuan penelitian ini yaitu diketahui hubungan pengetahuan, sikap ibu dan dukungan keluarga secara simultan dengan kunjungan balita di Posyandu Desa Marga Bhakti Kecamatan Sinar Peninjauan Kabupaten Ogan komering Ulu Tahun 2021.Metode Penelitian kuantitatif desain cross sectional. Di posyandu Desa Marga Bhakti Kecamatan Sinar Peninjauan Kabupaten Ogan komering Ulu Tahun 2021.Populasi semua ibu yang membawa balita ke posyandu dari bulan Januari – April berjumlah 89 balita dengan sampel  berjumlah 89 balita.analisa data univariate dan bivariate dengan chi square.Hasil responden yang berpengetahuan baik 76,9% berkunjung ke posyandu,pada sikap ibu yang positif terdapat 68,1% kunjungan balita ke posyandu, pada ibu yang mendapatkan dukungan 71,4% yang tidak mengkunjungi posyandu.Kesimpulan Ada hubungan dukungan keluarga secara simultan dengan dengan Kunjungan BalitaSaran dapat dijadikan sebagai bahan masukan untuk meningkatkan pelayanan kesehatan. Kata Kunci: Balita,Kunjungan,Posyandu ABSTRACT Background: Toddlers are included in a group that is at high risk of experiencing health problems. The data from the South Sumatra provincial health office showed the D/S coverage in 2018 has not reached the target of 85%, only reaching 73.2% (669,814 toddlers) out of 914,527 toddlers. This shows a decrease compared to 2017 (75.99%). The D/S coverage has not reached the target partly because the effectiveness of the activities of the integrated healthcare center and the activities outside the public health center has not been optimal. based on the data from the integrated healthcare centers in Marga Bhakti village targeting toddlers aged 0 – 5 years, there were 2.671 toddlers, and only 548 toddlers were brought to visit the integrated healthcare center. The impacts on children who do not routinely visit the integrated healthcare center are that their nutritional status is not monitored, they will suffer from diseases such as hepatitis, measles, and tuberculosis if they are not immunized, and most importantly, there will be an increase in cases of death of toddlers.Objective: to determine the relationship between the level of knowledge, mother's attitude, and family support simultaneously with toddlers’ visit at the integrated healthcare center in Marga Bhakti Village, Sinar Peninjauan District, Ogan Komering Ulu Regency in 2021Research Methods: Quantitative research method with a cross-sectional design was used in this study. The study was conducted at the integrated healthcare centers in Marga Bhakti Village, Sinar Peninjauan District, Ogan Komering Ulu Regency in 2021. The population in the study were all mothers who brought their toddlers to the integrated health center from January to April totaling 89 toddlers.  The sample of the study was 89 toddlers. Univariate and bivariate data analysis with chi-square statistical tests were used to analyze the data.Results: 76, 9 % of the respondents who had a good level of knowledge visited the integrated healthcare center. Regarding mothers' attitudes, 68,1 %  of the respondents who had good attitudes toward toddlers' visit at the integrated healthcare center visited the integrated healthcare center. Then, in terms of family support, 71, 4% of the respondents did not visit the integrated healthcare center.Conclusion: There was a relationship between the level of knowledge, the mother's attitude, and family support simultaneously with toddlers’ visit at the integrated healthcare centerSuggestion: the results of the study can be used as references and recommendations to improve health services Keywords: Toddlers, Visit, Integrated healthcare center